Factors Influencing Innovation Acceptance Online Banking Service of Krung Thai Bank Public Company limited in Muang District, Nakhon Si Thammarat Province - Wichaipon, Phannipa; Makka, Drinthip (Rajapark Journal, 2025)
The research aims to study personal factors, factors that influence innovation adoption, and acceptance of online banking service innovations that affect acceptance of online banking service innovations in the financial transactions of customers of Krung Thai Bank Public Company Limited. The sample group was Krung Thai Bank Public Company Limited customers in Mueang District, Nakhon Si Thammarat Province. The sample size was determined by W.G. Cochran’s formula, totaling 385 samples. Accidental sampling was used, and the statistics used were percentage, mean, standard deviation, t-test, one-way analysis of variance, LSD pairwise test, and multiple regression analysis. The research results found that 1) Most customers of Krung Thai Bank Public Company Limited are female, aged between 41 and 60 years, have a bachelor’s degree, work in government service/state enterprises, and have an average monthly income of 20,001 and 30,000 baht. 2) Factors influencing the acceptance of online banking innovation, the aspect with the highest average value was observability, and customers with different genders, ages, and average monthly incomes had different factors influencing the acceptance of online banking innovation overall. 3) Acceptance of online banking innovations, the aspect with the highest average value was perceived ease of use, and customers of different genders had different overall acceptance of online banking innovations. 4) Factors influencing the acceptance of online banking innovation, observability, increased benefits, complexity, and compatibility have a statistically significant relationship and influence on the acceptance of online banking innovation at the 0.05 level.